ULTRASTRUCTURAL CHANGES IN Schistosoma mansoni MALE WORMS AFTER in vitro INCUBATION WITH THE ESSENTIAL OIL OF Mentha x villosa Huds - MATOS-ROCHA, Thiago José; CAVALCANTI, Marília Gabriela dos Santos; VERAS, Dyana Leal; FEITOSA, Ana Paula Sampaio; GONÇALVES, Gabriel Gazzoni Araújo; PORTELA-JUNIOR, Nairomberg Cavalcanti; LÚCIO, Ana Silvia Suassuna Carneiro; SILVA, Anekécia Lauro da; PADILHA, Rafael José Ribeiro; MARQUES, Márcia Ortiz Mayo; BARBOSA-FILHO, José Maria; ALVES, Luiz Carlos; et al. (Revista do Instituto de Medicina Tropical de São Paulo, 2016)
Introduction: The essential oil Mentha x villosa (MVEO) has a wide range of actions, including antibacterial, antifungal, antiprotozoal and schistosomicidal actions. The present study aimed to investigate the ultrastructural changes of MVEO on the tegument of adult Schistosoma mansoni. Materials and Methods: Different concentrations of MVEO were tested on S. mansoni adult worms in vitro. Ultrastructural changes on the tegument of these adult worms were evaluated using scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Results: The MVEO caused the death of all worms at 500 μg mL-1 after 24 h. After 24h of 500 μg mL-1 MVEO treatment, bubble lesions were observed over the entire body of worms and they presented loss of tubercles in some regions of the ventral portion. In the evaluation by TEM, S. mansoni adult worms treated with MVEO, 500 μg mL-1, presented changes in the tegument and vacuoles in the syncytial matrix region. Glycogen granules close to the muscle fibers were visible. Conclusion: The ability of MVEO to cause extensive ultrastructural damage to S. mansoni adult worms correlates with its schistosomicidal effects and confirms earlier findings with S. mansoni.